MO778: Influence of Therapy on the Duration of First Arteriovenous Fistula in Haemodialysis Patients—A Multicenter Longitudinal Study. (3rd May 2022) - Knezevic, Violeta; Azasevac, Tijana; Celic, Dejan; Petkovic, Dobrila; Paunic, Zoran; Dudic, Svetlana; Stolic, Radojica; Radovic, Milan; Vavic, Neven; Zivanov, Dusan
Abstract: BACKGROUND AND AIMS: A 5-year research was conducted on haemodialysis patients with the aim to determine the effect of therapy on the patency of arteriovenous fistula (AVF) for haemodialysis. METHOD: The study included 338 haemodialysis patients with the incidence of the creation of AVF in 2014. Patients were divided into two groups, according to the duration time of AVF namely short-term (≤6 months) and long-term (>6 months) patency. Clinical and laboratory parameters were analysed as well as type and frequency of complications, characteristics of AVF and treatment. The data were analysed with a chi-squared test, ANOVA test and an ordinally logistic regression. There was a statistical significance, P <0.05. RESULTS: From a total of 338 patients, the average age of 59.06 ± 12.45, 66.6% of patients were men. 80.7% of the patients were in the short-term group. Patients taking anti-platelet drugs make 14.8%, patients taking anticoagulation therapy and double anti-platelets therapy make 1.8%, patients taking statins, angiotensin-converting enzyme inhibitors (ACE)/angiotensin-receptor blockers (ARB) and calcium channel blockers make 47% and 2.6% of patients took no medication. The number of AVF complications was thrombosis in 19.1%, haemorrhage in 1.9%, aneurism and pseudoaneurysm in 0.5%, 'Steal' syndrome in 0.3%, infections in 0.3% and other complications in 2.2%. In accordance with the length of anti-platelets therapy (˂30 days, between 30 and 90 days, and ˃90 days) after the creation of AVF, it was concluded that the most influential effect was in the period between 30 and 90 days after creation. Patients with AVF for ˂6 months had significantly more vascular calcifications (P =.0017). The groups did not differ in the length of anti-platelets and anti-coagulation therapy before the creation of AVF (<1 year, >1 year, no therapy), time of maturity of AVF (4–6 weeks, 6–8 weeks, ˃8 weeks), indications for reducing or stopping with anti-platelets or anticoagulation therapy in the moment of AVF creation. Four models of ordinally logistic regression (2015, 2016, 2017, 2018) were created in which the dependent variables were the complications of AVF by years, the factors were the type of treatment and the frequency of each complication for each year, while the covariate was the number of months after the AVF creation (Table). CONCLUSION: Patients that started taking anti-platelets drugs from 30 to 90 days of AVF, had AVF for a significantly longer time. The model showed in years states that the frequency of complications decreases over time and that there are more infections and other complications than thrombosis and haemorrhage.